Foucault e o liberalismo - Luiz Felipe Martins Candido (2020)
This work aims to present an interpretation of the treatment given by Michel Foucault to the theme of liberalism. This theme was posed as a problem by the philosopher in the period between the years 1976 and 1979. This period of Foucault’s thought, although not in discontinuity with his earlier or later thinking, has specific characteristics. During the 1970’s, Foucault build a broad set of reflections on power. He has developed studies on specific ways of the exercise of power, evidencing his dispersion in the body of society. Foucault’s reflections on power led him to consider the problems concerning the concept of “government”. For Foucault, “government” is a broad concept that, in the texts of the period considered, defines the exercise of power itself in a general way, consisting in the conduct of conducts of individuals or groups over others. In the second half of the 1970’s Foucault coined the term “governmentality” to approach the specifically political aspects of the government. If governing comprises a variety of situations, one of the areas in which this action or set of actions is more prominent is that of politics. For the philosopher, the governmentality consists in the set of methods, procedures, concepts, and theories established to governing the new object that the politics has given to itself in the modernity, the population, understood as a set of human beings thought in terms of their vital characteristics. In his investigations on governmentality, Foucault finds a variety of ways of exercise of power defined for the government of populations. In the mosaic of theories and practices built by Foucault, the liberal way of governing stands out in the course of 1979. For the philosopher, liberalism was constituted in modernity as a way of governing which main characteristic was critique and the attempt to limit the very action of governing. In this sense, liberalism, both in its classical version and in its neoliberal version, developed a series of theoretical and practical tools aimed at allowing a government able to better managing the life of populations based on the delimitation of new areas of intervention on reality such as the market and the civil society. We will seek to approach each of these elements in order to grasp the meaning established by Foucault and, at the same time, define an interpretive approach of the notions defined by Foucault in reference to the historical context of the development of the philosopher’s course. We will also give a critical treatment to the problem of the insertion of these themes in the more general context of his philosophy, discussing the kind of approach that the philosopher may or may not have had of these currents of thought.